FGF12 (Fibroblast Growth Factor 12) Inhibits Vascular Smooth Muscle Cell Remodeling in Pulmonary Arterial Hypertension - Yeo, Yeongju; Yi, Eunhee S.; Kim, Jeong Min; Jo, Eun Kyung; Seo, Songyi; Kim, Ryul I.; Kim, Koung Li; Sung, Jong Hyuk; Park, Sang Gyu; Suh, Wonhee (Hypertension, 2020)
Loss of BMP (bone morphogenic protein) signaling induces a phenotype switch of pulmonary arterial smooth muscle cells (PASMCs), which is the pathological basis of pulmonary vascular remodeling in pulmonary arterial hypertension (PAH). Here, we identified FGF12 (fibroblast growth factor 12) as a novel regulator of the BMP-induced phenotype change in PASMCs and elucidated its role in pulmonary vascular remodeling during PAH development. Using murine models of PAH and lung specimens of patients with PAH, we observed that FGF12 expression was significantly reduced in PASMCs. In human PASMCs, FGF12 expression was increased by canonical BMP signaling. FGF12 knockdown blocked the antiproliferative and prodifferentiation effect of BMP on human PASMCs, suggesting that FGF12 is required for the BMP-mediated acquisition of the quiescent and differentiated PASMC phenotype. Mechanistically, FGF12 regulated the BMP-induced phenotype change by inducing MEF2a (myocyte enhancer factor 2a) phosphorylation via p38MAPK signaling, thereby modulating the expression of MEF2a target genes involved in cell proliferation and differentiation. Furthermore, we observed that TG (transgenic) mice with smooth muscle cell-specific FGF12 overexpression were protected from chronic hypoxia-induced PAH development, pulmonary vascular remodeling, and right ventricular hypertrophy. Consistent with the in vitro data using human PASMCs, FGF12 TG mice showed increased MEF2a phosphorylation and a substantial change in MEF2a target gene expression, compared with the WT (wild type) controls. Overall, our findings demonstrate a novel BMP/FGF12/MEF2a pathway regulating the PASMC phenotype switch and suggest FGF12 as a potential target for the development of therapeutics for ameliorating pulmonary vascular remodeling in PAH.
Keywords: Animals; Bone Morphogenetic Proteins; Cell Proliferation; Cells, Cultured; Fibroblast Growth Factors; Humans; Male; MAP Kinase Signaling System; MEF2 Transcription Factors; Mice, Inbred C57BL; Mice, Transgenic; Muscle, Smooth, Vascular; Myocytes, Smooth Muscle; Pulmonary Arterial Hypertension; Pulmonary Artery; Rats, Sprague-Dawley; Vascular Remodeling; animals; cell differentiation; cell proliferation; hypoxia; pulmonary arterial hypertension